Eating behavior and the consequences of depression (Research, Society and Development, 2022)
Eating behavior goes beyond counting macronutrients or obtaining energy, it is present from the choice of food, as well as the choice of where to eat and in the company of who. And taking this definition into account, it can be seen that the emotional state is also part of the moment of the meal, and this is what some studies have shown, analyzing patients diagnosed with depression and the influence of food on the symptoms of the disease. Based on the theme addressed, the present study aimed to review the literature, seeking to understand and highlight the existence of a relationship between symptoms of depression and changes in eating behavior in diagnosed individuals. It was found that the frequent consumption of ultra-processed foods allows the predominance of depressive symptoms, that an anti-inflammatory diet comes as a strong ally to the treatment, as it aims to improve the quality of life of patients and helps to reduce the symptoms of the disease and it was possible to conclude that nutrition is able to act as one of the main allies in the treatment of depression through a healthy diet, by providing the nutrients necessary to improve the functioning of the vital systems of patients with depression.